2007
DOI: 10.1007/s10620-006-9119-z
|View full text |Cite
|
Sign up to set email alerts
|

Thiopurine Methyltransferase Activity in Spain: A Study of 14,545 Patients

Abstract: We sought to assess the activity of thiopurine methyltransferase (TPMT) in 14,545 Spanish patients with different diseases amenable to treatment with azathioprine/6-mercaptopurine (6-MP), and to evaluate the proportion of patients with low TPMT activity and therefore a higher risk of myelotoxicity with these drugs. TPMT activity in red blood cells (RBCs) was measured by a radiochemical method. The association between several clinical variables and TPMT activity was assessed by multiple linear regression. We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
46
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 40 publications
4
46
0
2
Order By: Relevance
“…26 The cost for determining TPMT by this method is h40 per determination. Assuming a rate of 1:200 for TMPT deficiency 24 one arrives at a highend average cost of h8000 per identified TPMT-deficient individual for Spain (Table 2). Wider application of TPMT testing in Spain would likely lead to substantially reduced costs.…”
Section: Methodsmentioning
confidence: 99%
“…26 The cost for determining TPMT by this method is h40 per determination. Assuming a rate of 1:200 for TMPT deficiency 24 one arrives at a highend average cost of h8000 per identified TPMT-deficient individual for Spain (Table 2). Wider application of TPMT testing in Spain would likely lead to substantially reduced costs.…”
Section: Methodsmentioning
confidence: 99%
“…99 Prevalence of TPMT activity originated from a population-based cohort study of the distribution of phenotypic TPMT activity in 14,545 Spanish patients with diseases amenable to treatment with azathioprine. 101 Gisbert and colleagues 101 found that TPMT activity was low in 0.5% of the cohort, intermediate in 11.9% and high in 87.6%. Treatment efficacy was assessed through disease progression, defined by a decline in FVC of at least 10%.…”
Section: Modelling Approachmentioning
confidence: 99%
“…11. Low TPMT activity and high 6-TGN concentrations have been linked to therapeutic success and myelosuppression in IBD patients treated with thiopurines [3,8]. Yet, none of these metabolites or activities was measured in the study.…”
mentioning
confidence: 97%